SIMULATION OF FATIGUE AND DEFORMATION OF CARBON FIBER DRONE PROPELLERS USING THE FINITE ELEMENT METHOD (FEM) - Arif, Syaiful (Otopro, 2026)
This study analyses finite elements in the structural calculation of a drone propeller in carbon fiber with loads that represent live use. The output of this study evaluates the effect of load variations on deformation, stress distribution, and safety factors as key indicators of structural performance. A three-dimensional propeller model is developed based on the actual geometric configuration and analysed using the Finite Element Method (FEM). Several loadings are considered: a base load with a total mass of 3.6 kg, and two additional loading conditions with increasing masses of 0.5kg and 0.75kg. The applied loads are converted into equivalent forces distributed along the propeller blades to simulate realistic operating conditions. Simulations show that increasing the applied load causes a proportional increase in the maximum deformation and a significant reduction in the minimum safety factor. The maximum deformation increases from 14.933mm at the base load to 18.044mm at the highest load. The blade tip is consistently identified as a critical region, where the highest deformation and stress concentration occur due to bending-dominated behaviour. The safety factor ranges from 0.51341 to 0.42489 as the load increases, indicating a decrease in structural safety. Fatigue loading is mentioned, this study addresses fatigue qualitatively based on stress concentration and safety factor trends, as explicit S–N curve data, load cycle definitions, and mean stress corrections are not included. The results emphasize the importance of structural optimization and accurate material modelling to improve the reliability and durability of carbon fiber drone propellers under various load conditions.